Perspectives on regional integration and co-operation in East Africa : proceedings (Secretariat of the Commission for East African Co-operation ArushaTZ, 2000)
Presents speeches and background papers presented at the First Ministerial Seminar on East African Cooperation. Reflects the spirited mood of the time when East Africans expressed themselves freely and frankly on the Draft Treaty for the Establishment of the East African Community, and the type of regional integration arrangement they wanted.
Additional copy located in the Office of the Secretary-General